A critical review on automation of steering mechanism of load haul dump machine. (February 2020) - Rowduru, Sreeharsha; Kumar, Niranjan; Kumar, Ajit
This article presents a brief note on the evolution of steering mechanisms and more emphasized on articulated steering system of the load haul dump machine. In this respect, pictorial representation of the evolution of steering mechanisms for on-road and articulated steering mechanisms of the load haul dump machine is made from the available literature. Critical review on basic elements required for the complete automation of the load haul dump vehicle steering system is presented. Different types of controllers for path tracking error minimization of the scale-modeled or simulated model of the load haul dump steering system are tabulated. Few case studies stimulating the complete automation of the load haul dump steering system employed on the field are also discussed. Challenges and some research gaps in making fully automated steering system of the load haul dump machine are identified in this review article. At the end, based on the critical review, some novel methods for making the fully automated steering system of the load haul dump machine is provided, which is the potential future work for the design and development of feasible automatic steering system.